2019
DOI: 10.1021/acsaem.9b01803
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity and Mechanisms in Fluoride Shuttle Battery Reactions: Difference between Orthorhombic and Cubic BiF3 Single Microparticles

Abstract: BiF3 is a strong candidate for a cathode material in fluoride shuttle batteries (FSBs), which utilize defluorination of metal fluorides and fluorination of metals. Much interest has been shown in FSBs as next-generation batteries with high energy densities. Elucidation and control of reactivity and mechanisms in FSB reactions are crucial for the development of FSBs with high performances. In the present work, structural transformation, reactivities, and mechanisms in FSB reactions of BiF3 microparticles partly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 31 publications
(60 reference statements)
2
28
2
Order By: Relevance
“…Apart from using Bi/BiF3 as a cathode in an all-solid-state modification, it has also been used as the cathode in a liquid electrolyte system. In 2019 Yamanaka et al reported 131 on using orthorhombic-BiF3 microparticles in a gold plating film as a cathode material against Pb wire as the counter electrode. Then the structural transformation and reaction mechanisms within BiF3 as the active electrode material were studied by means of in-situ Raman microscopy.…”
Section: Conversion-based Cathode Materialsmentioning
confidence: 99%
“…Apart from using Bi/BiF3 as a cathode in an all-solid-state modification, it has also been used as the cathode in a liquid electrolyte system. In 2019 Yamanaka et al reported 131 on using orthorhombic-BiF3 microparticles in a gold plating film as a cathode material against Pb wire as the counter electrode. Then the structural transformation and reaction mechanisms within BiF3 as the active electrode material were studied by means of in-situ Raman microscopy.…”
Section: Conversion-based Cathode Materialsmentioning
confidence: 99%
“…However, the mapping of the electrolyte did not change significantly in this defluorination process, as shown in Figure 2c−f, also suggesting the direct mechanism. During these processes, nonelectrochemical transformation of o-BiF 3 to c-BiF 3 , which was previously observed in an ionic-liquid electrolyte, 33 was not observed (see also Figure S1 in the Supporting Information. ).…”
Section: ■ Results and Discussionmentioning
confidence: 73%
“…These results indicate that defluorination of c-BiF 3 is slower than that of o-BiF 3 , being consistent with previously reported results obtained by using an ionic-liquid electrolyte. 33 However, defluorination of both o-BiF 3 and c-BiF 3 occurred at lower voltages (below 0.3 and 0.15 V, respectively) than those in the ionic-liquid electrolyte (0.45 and 0.2 V, respectively). 33 In addition, the current corresponding to defluorination for (o, c)-BiF 3 /gold (Figure 2b) was one order lower than that in the ionic-liquid electrolyte (Figure 5b in ref 33).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Fluoride-shuttle batteries, which utilize fluoride ion (F – ) transfer between electrodes, are one of the candidates as next-generation batteries due to their potential to achieve higher energy density than the lithium-ion batteries. , The concept of this battery was reported in 1970s. , Reddy and Fichtner in 2011 demonstrated the first reversible cycling performance in an all-solid-state fluoride-shuttle battery, and it has attracted significant attention ever since. There are many types of metal/metal fluorides, thus making it possible to achieve a high voltage cell by exploring suitable combinations of cathode and anode materials with an appropriate fluoride ion conductivity electrolyte. Then, in a defluorination process based on a conversion reaction of metal/metal fluorides in the electrodes, multiple electron reactions can be promoted by moving single-charged anions of F – in electrolytes.…”
Section: Introductionmentioning
confidence: 99%